The Benedictine revival in the north: the last bulwark of Anglo-Saxon monasticism? - Dawtry, Anne F. (Studies in church history, 1982)
The midland houses of Winchcombe and Evesham restored monasticism to the north in a fervent and wholly English form. No one can read the history of this migration and the subsequent history of Durham without feeling that here, at least, English monastic life was sound.’In these words, Knowles summed up his view of the type of monastic observance which was instituted in the houses of the northern renovatio after the Norman Conquest. Certainly there were important Anglo-Saxon elements present in the revival of Benedictine monasticism in the north of England; Durham, Whitby and St Mary’s, York, owed much to the Anglo-Saxon monastic life as retained at Worcester and Evesham after the Norman Conquest.